Defining Dysphoric Milk Ejection Reflex: using Premenstrual Dysphoric Disorder as a framework for proposing preliminary diagnostic criteria - Howard, Megan; Davoudian, Teni; Cirino, Nicole H. (Frontiers in Psychiatry, 2026)
Dysphoric Milk Ejection Reflex (D-MER) is a distinct neurobiological condition characterized by negative alterations in mental state in response to milk letdown during lactation. Symptoms vary by patient and can include feelings of sadness, anxiety or agitation. Importantly, the symptoms are brief, typically lasting no more than 5 minutes. Prevalence has been found between 6 and 27% of lactating women, but studies show heterogeneity, due in part to inconsistent definition. D-MER is not currently classified in the Diagnostic and Statistical Manual of Mental Disorders (DSM) or the International Classification of Diseases (ICD), which presents a challenge for researchers of the condition. The pathophysiology of D-MER is not well understood, but may be mediated by hormonal changes. In an attempt to begin to formalize classification of this condition, the authors explore the association with another recently classified, hormonally mediated and time sensitive condition: premenstrual dysphoric disorder or PMDD. Like D-MER, PMDD is characterized by heterogeneous symptoms that occur on a predictable timeline. The recent addition of a formal diagnostic category into the DSM helped facilitate an expansion of research into etiology and treatment of the condition. This paper will explore a pathway to classification of D-MER based on the current research using the framework of the DSM-5 diagnostic criteria for PMDD. We will conclude by outlining future research priorities that will help to better define this condition and differentiate it from other causes of emotional distress during lactation.